Study of structure, morphology, optical absorption, and gap modulation of Activated carbon (AC) / NiO, Fe3O4, and Co3O4 oxide nanocomposites - A. Haghir Ebrahim Abadi; M. M. Bagheri-Mohagheghi (Progress in Physics of Applied Materials, 2023)
In this paper, the synthesis and structural and optical properties of activated carbon /metal oxide nanocomposites have been studied for energy storage applications. Activated carbon / nickel oxide, activated carbon / iron oxide, and activated carbon / cobalt oxide nanocomposites were synthesized by green synthesis from carbonaceous waste and their structural and optical properties were investigated. The prepared nanocomposites were characterized by X-ray diffraction (XRD), UV-Vis optical absorption spectroscopy, Scanning Electron Microscopy (SEM), Transmission Electron Microscopy (TEM), and Fourier-transform infrared (FTIR) spectroscopy techniques. The XRD results of the activated carbon / metal oxide nanocomposites, in addition to the activated carbon background, show a polycrystalline phase corresponding to NiO, Fe3O4, and Co3O4 oxides. According to SEM images, a carbon porous background was observed in nanocomposites, which is filled with metal oxide nanoparticles and these nanoparticles present on its surface non-uniformly. The band gap results of nanocomposites showed the presence of two shoulders clearly indicating the presence of two components in the nanocomposite, i.e., activated carbon (3.62-4.65 eV) and metal oxide (3.0 eV- 4.25 eV). In FTIR analysis, in addition of the carbon-carbon bonds, specific peaks were observed in the range of k=400-700 cm-1, indicating that AC/ metal oxide nanocomposites have been successfully synthesized.